Transformasi Polopalo sebagai Media Hiburan Masyarakat Gorontalo di Lihuta Lo Polopalo - Rahmawati Ohi; Ary Nugraha Wijayanto (Ideas Publishing, 2023)
Transformation polopalo as an entertainment medium, especially in the case of lihuta lo polopalo experiences a use-value remodeling conflict. The existence of conflict results in the degradation of functions and preservation. Base on the conflict so the purpose of this study is to describe the transformation of polopalo as an entertainment medium for the people of Gorontalo in the context of lihuta lo polopalo. The research method uses case study ethnography. The results of the study show that the Transformation of polopalo has an impact on the chronobiology relations of its manifest-latency function on aspects of entertainment, such as physical, aesthetic, economic, social and cultural values.